The Effect of Work Discipline, Organizational Commitment and Work Motivation on Employee Performance of the Directorate General of Construction Development Minister For Public Works and Housing Republic of Indonesia - Cendi Chrisnanto; Setyo Riyanto (International Review of Management and Marketing, 2020)
Work discipline, organizational commitment, and work motivation are often linked in studies of employee performance in both private and government organizations. Data collection was carried out by distributing questionnaires using the Linkert scale, the population of which came from 287 people from the Directorate General of Construction Management, Ministry of Public Works and Housing. The selected sample was calculated using the Slovin formula and obtained a sample of 137 respondents. Hypothesis testing in this study uses the validity test, reliability test, classic assumption test, multiple linear regression analysis, and the correlation between dimensions with SPSS version 22. The results show that discipline, organizational commitment, and work motivation variables have positive and significant effects on employee performance.